Development and Validation of a Reversed-Phase HPLC Method for the Analysis of Budesonide in Pharmaceutical Dosage Forms - Krishnaiah, Y.S.R.; Shyale, S.S.; Bhaskar, P.; Srinivasa Rao, G. (Asian Journal of Chemistry, 2010)
A rapid and sensitive high-performance liquid chromatographic method was developed for the estimation of budesonide in pharmaceutical dosage forms. Budesonide was chromatographed on a reverse phase C-18 column using nimesulide as internal standard in a mobile phase consisting of methanol and water in the ratio of 80: 20 v/v. The mobile phase was pumped at a flow rate of 0.8 mL/min, and the eluents were monitored at 241 nm. The calibration curve was linear in the range of 0.1 to 40 g/mL. The intra- and inter-day variation was found to be less than 1% showing high precision of the assay method. The mean recovery of the drug from the solutions containing 5, 10 or 20 μg/mL was 98.47 ± 0.37% indicating high accuracy of the proposed HPLC method. Due to its simplicity, rapidness, high precision and accuracy, the proposed HPLC method may be used for determining budesonide in bulk drug samples or in capsules.